Work Environment, Work Discipline, and Interpersonal Communication to Improve Hotel Employee Performance: The Mediating Role of Sustainable Collaboration Sebagai Mediator - Mulyaningsih, Sri Purnami; Riyanto, Agus; Silitonga, Parlagutan (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This research aims to find out and obtain empirical evidence regarding the influence of Capital Structure, Business Growth, and Tax Planning on company value. This research is included in the type of associative quantitative research. The population in this research is properties & real estate sector companies listed on the Indonesia Stock Exchange for the 2017-2022 observation period. Sampling was carried out using purposive sampling technique. The data obtained was analyzed using multiple linear regression using E-views 12 software. The results of this research show that simultaneously Capital Structure, Business Growth and Tax Planning have an influence on Company Value. Partially, Capital Structure and Tax Planning have no effect on Company Value. Meanwhile, business growth partially has an influence on company value.